Discovering quantum circuit components with program synthesis - Sarra, Leopoldo; Ellis, Kevin; Marquardt, Florian (Machine Learning: Science and Technology, 2024)
Despite rapid progress in the field, it is still challenging to discover new ways to leverage quantum computation: all quantum algorithms must be designed by hand, and quantum mechanics is notoriously counterintuitive. In this paper, we study how artificial intelligence, in the form of program synthesis, may help overcome some of these difficulties, by showing how a computer can incrementally learn concepts relevant to quantum circuit synthesis with experience, and reuse them in unseen tasks. In particular, we focus on the decomposition of unitary matrices into quantum circuits, and show how, starting from a set of elementary gates, we can automatically discover a library of useful new composite gates and use them to decompose increasingly complicated unitaries.
CRIS-Team Scopus Importer:2024-05-17
Keywords: machine learning; program synthesis; quantum circuits; quantum physics